Pengendalian Suhu dan Kelembapan Sistem Aeroponik Tanaman Stroberi Berbasis IOT Menggunakan Fuzzy Logic - Fitria Suryatini; Wahyudi Purnomo; Maya Delistiani (Pusat Pengembangan, Penelitian dan Pengabdian kepada Masyarat (P4M) Politeknik Manufaktur Bandung (Polman Bandung), 2020)
Planting conventional strawberry plants is quite difficult because it requires space, labor, water, and fertile land. Therefore, planting plants without soil can be applied. The aeroponic system is a planting method that lets the roots hanging in the air then sprayed with nutrients. It could reduce water consumption, fertilizer, and land maximization. The mist nozzle controlled by a microcomputer with Fuzzy logic will spray the plant with a temperature and humidity sensor input. Root nutrient controlled by the on-off method. LED is controlled according to time. The system can be monitored and controlled with an Android interface called Blynk. The results of this study are the achievement of the average value of the root zone temperature is 23.3 ℃ from 18-30 ℃, and the crown temperature 21.5 ℃ from 14-25 ℃. Besides, root and crown moisture is also included in the 85-95% range, namely 89% and 93%. Monitoring and control systems can be done remotely using the Blynk application.